Productive performance of Canchim and Nelore females. I. Growth and puberty - Alencar, Maurício Mello de; Costa, José Ladeira da; Corrêa, Luciano de Almeida (Pesquisa Agropecuaria Brasileira, 2014)
Seventy Canchim and Nelore weaned calves were reared, all together, on pasture, in the State of São Paulo, Brazil, to evaluate the productive efficiency of the Canchim breed. This work presents the results related to body weight and to age and weight at puberty and breeding. Age at puberty was considered as the age at first estrus and breeding age as the age of the second or third estrus; depending on whether the animal showed a normal or abnormal cycle, respectively. The analyses of covariance showed significant effects (P<0.05 or P<0.01) of breed for body weights, with the Canchim being 5.8%, 6.5%. 9.1% and 16.8% heavier at twelve, 18, 24 and 30 months of age, respectively. The least square means for the Canchim and Nelore females were, in the same order. 164kg and 155 kg, 230 kg and 216 kg, 276 kg and 253 kg, 389 kg and 333 kg respectively. The ages at puberty and of breeding were, on the average, 730 ± 17 and 867 ± 15 days for the Canchim, and 772 ± 17 and 899 ± 16 days for the Nelore heifers, while the weights were, in the same order, 293 ± 7 kg and 347 ± 6 kg, and 282 ± 7 kg and 323 ± 6 kg. Of these, only for weight at breeding time were the differences between breeds significant (P<0.01).